MCQs & OBAs in obstetrics & gynaecology the leaked questions with answers & comments - Al-Kubaisi, Muna Khaleel Dheyab (Noor Publishing, 2018)
This book is a useful tool for building up knowledge for Medical undergraduate students in the field of obstetrics and gynecology as well as a way for students to familiarise themselves with the topics that are usually covered in an exam. It contains two types of questions which are multiple choice and one based answer questions provided with essential feedback and justifications to the answers.